The Dutch timber trade on the river Elbe in the seventeenth and eighteenth centuries (Bulletin KNOB, 2015)
Not long after the Brandenburg timber port relocated from Hamburg to Harburg in 1661, there developed a brisk trade with the Dutch market, which really took off after 1664, when the first Dutch timber merchant set up business there. Whereas Harburg had initially supplied timber for shipbuilding and coopering, there now was a significant increase in the trade in construction timber. By around 1680 there were several Dutch merchants active in the timber trade here, who mostly did their own timber buying upriver and transported the logs to Harburg with their own rafts. This practice continued into the eighteenth century, although rafts owned by timber traders from the March of Brandenburg, Saxony, Anhalt and Mecklenburg also came to Harburg. Around 1720 there were even timber consignments from the many-branched network of the River Warta deep in Poland and from Silesia, although Harburg was starting to experience competition as a timber port from Stettin.Around 1694, the limited space in the Harburg harbour led to the relocation of the timber port to a nearby anabranch of the River Elbe, the ‘Reiherstieg’, where it continued to develop. By 1720 it was loading over 300, mainly Dutch timber carriers a year. Shipbuilding timber had once again become the core business, although it  no longer included much knee timber, which had become so scarce in the region that its export was even banned for a while from 1665 onwards.Interestingly, some timber merchants actually invested in the expansion of the Harburg harbour and in the new harbour at Reiherstieg. On the other hand, they also threatened to take their trade elsewhere, in some cases even supported by trading partners in the trading areas, in an attempt to influence investment in the harbours. Owing to this pressure and to competition from a new raft harbour constructed in 1725 in the nearby Danish city of Altona, the winter harbour the timber merchants had been calling for since the late seventeenth century was built on the Reiherstieg. Henceforth the rafts that arrived too late for transhipment could be moored here in autumn to await the coming spring.In the early decades of the eighteenth century the flourishing timber port in Harburg was dominated by several Dutch merchants from Zaandam. With their need for employees, they played a key role in the local labour market and the tolls paid were an important source of income for the regional administration (‘Amtsverwaltung’).